Green Preparation of Durian Rind-Based Cellulose Nanofiber and Its Application in Aerogel - Huwei Xing; Yongsheng Fei; Jingru Cheng; Congcong Wang; Jingjing Zhang; Chenxi Niu; Qian Fu; Jiali Cheng; Lingbin Lu (Molecules, 2022)
In this study, a green, highly efficient and low energy consumption preparation method of cellulose nanofiber (CNF) was developed by using agricultural and forestry waste durian rinds as raw materials. The power of ultrasonic treatment was successfully reduced to only 360 W with low molecular weight liquid DMSO. The obtained durian rind-based CNF had a diameter of 8–20 nm and a length of several micrometers. It had good dispersion and stability in water, and could spontaneously cross-link to form hydrogel at room temperature when the concentration was more than 0.5%. The microscopic morphology and compressive properties of CNF aerogels and composite cellulose aerogels prepared from durian rind-based CNF were evaluated. It was found that CNF could effectively prevent the volume shrinkage of aerogel, and the concentration of CNF had a significant effect on the microstructure and mechanical properties of aerogel. The CNF aerogel with 1% CNF exhibited a sheet structure braced by fibers, which had the strongest compression performance. The porosity of CNF aerogels was high to 99%. The compressive strength of the composite cellulose aerogel with durian rind-based CNF was effectively enhanced.